Labor and Delivery Outcomes with the Sequential Use of Misoprostol Followed by Cervical Foley Catheter - Hopkins, Maeve K.; Hamm, Rebecca F.; Srinivas, Sindhu K.; Levine, Lisa D. (American Journal of Perinatology, 2020)
Objective Studies demonstrate shorter time to delivery with concurrent use of misoprostol and cervical Foley catheter. However, concurrent placement may not be feasible. If misoprostol is used to start an induction, little is known regarding the benefit of sequentially using Foley catheter. We examine obstetrical outcomes in women with Foley catheter placed after misoprostol compared with those only requiring misoprostol.Study Design Retrospective cohort study of singleton pregnancies, intact membranes, and an unfavorable cervix (Bishop score of ≤6 and dilation ≤2 cm) undergoing term induction May 2013 to June 2015. We compared obstetrical outcomes between women receiving misoprostol alone versus those that had a Foley catheter placed after misoprostol. Outcomes are mode of delivery, time to delivery, chorioamnionitis, admission to neonatal intensive care unit, and maternal morbidity. Chi-square and Fisher's exact tests were used for categorical variables, Mann–Whitney U-tests compared continuous variables.Results Among 364 women, 281 began induction with misoprostol alone. A total of 135 (48%) subsequently had a Foley catheter placed. Characteristics were similar between the groups, although nulliparity and cervical dilation <1 cm at start of induction were more likely to have subsequent Foley catheter. Women with Foley catheter placement after misoprostol had a longer median time to delivery (15 vs. 11 hours, p < 0.001), twofold higher rate of cesarean (42 vs. 26%, odds ratio: 2.1, 95% confidence interval: 1.26–3.44, p = 0.004), and increased risk of neonatal intensive care unit (NICU) admission (21 vs. 11%, p = 0.024). There was a nonsignificant increased risk of chorioamnionitis (12 vs. 7%, p = 0.1) and maternal morbidity (15 vs. 8%, p = 0.08) in the misoprostol followed by Foley catheter group.Conclusion In women receiving misoprostol for induction, nulliparas and those with dilation <1 cm are more likely to have subsequent Foley catheter placement. Sequential use of cervical Foley catheter after misoprostol is associated with longer labor, higher cesarean rate, and increased NICU admission. Requirement of Foley catheter after misoprostol confers higher risk and may guide counseling.Key Points
Keywords: Induction; cervical ripening; misoprostol; Foley; neonatal morbidity